Enzymatic production of xylooligosaccharides from corn cobs : Assessment of two different pretreatment strategies - Capetti, Caio (2023)
Corn cobs (CCs) are abundant xylan-rich agricultural wastes. Here, we compared CCs XOS yields obtained via two different pretreatment routs, alkali and hydrothermal, using a set of recombinant endo- and exo-acting enzymes from GH10 and GH11 families, which have different restrictions for xylan substitutions. Furthermore, impacts of the pretreatments on chemical composition and physical structure of the CCs samples were evaluated. We demonstrated that alkali pretreatment route rendered 59 mg of XOS per gram of initial biomass, while an overall XOS yield of 115 mg/g was achieved via hydrothermal pretreatment using a combination of GH10 and GH11 enzymes. These results hold a promise of ecologically sustainable enzymatic valorization of CCs via “green” and sustainable XOS production.